Blood hydrogen peroxide break-down activity in healthy subjects and in patients at risk of cardiovascular events. (July 2018) - Carnevale, Roberto; Nocella, Cristina; Pignatelli, Pasquale; Bartimoccia, Simona; Stefanini, Lucia; Basili, Stefania; Novo, Marta; D'Amico, Alessandra; Cammisotto, Vittoria; Pastori, Daniele; Violi, Francesco
Abstract: Background and aims: Antioxidant status has been shown to be associated with cardiovascular events (CVEs). The aim of the study was to develop an assay measuring serum hydrogen peroxide (H2 O2 ) break-down activity (HBA) of healthy subjects (HS) and to validate it in a cohort of patients with atrial fibrillation (AF). Methods: We developed the HBA assay in 121 HS and validated it in 842 AF patients. The occurrence of CVEs was registered and correlated with HBA in AF during a median follow-up of 30.6 months (3226 patient-years). A combined endpoint of CVEs included fatal/non-fatal ischemic stroke and myocardial infarction, cardiovascular death and transient ischemic attack. Results: In HS, median HBA was 61.2% [IQR: 52.9–69.4]. AF patients disclosed lower HBA than 30 HS balanced for age and sex (48.6% [IQR: 24.7–65.1] vs. 59.4% [IQR: 49.2–66.2], p < 0.001). During a mean follow-up of 30.6 months (3226 patient-years), 168 CVEs occurred (5.2%/year). A multivariable Cox's proportional hazards regression analysis showed that age group 3 (71–80 years, HR:5.419, p = 0.020), age group 4 (>80 years, HR:9.783, p = 0.002), diabetes (HR:1.464, p = 0.049), previous cardiac events (HR:1.887, p = 0.001) and HBA (below median, HR:2.313, p < 0.001) predicted CVEs. Conclusions: We developed an easy assay to measure serum HBA, which was associated with CVEs in AF patients. This assay may represent an additional useful tool for cardiovascular risk stratification and should be validated in other high-risk populations. Highlights: We developed an easy assay to measure serum hydrogen peroxide break-down activity (HBA) 121 healthy subjects. We validated the HBA assay on 842 atrial fibrillation patients. The HBA assay may represent an additional useful tool for cardiovascular risk stratification.